2023
DOI: 10.3390/nu15143217
|View full text |Cite
|
Sign up to set email alerts
|

Fish Consumption during Pregnancy in Relation to National Guidance in England in a Mixed-Methods Study: The PEAR Study

Abstract: Guidance on foods to limit or avoid in pregnancy is provided on the NHS website for England. Advice on fish consumption is related to exposure to mercury, dioxins and polychlorinated biphenyls, which may have adverse effects on fetal neurodevelopment. Our aim was to provide evidence on the effectiveness of the guidance in minimising exposure to toxins while maximising nutrient intake in a mixed-methods study. An online questionnaire on fish consumption before/during pregnancy was completed by postpartum women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Subsequent survey research by FDA also indicated that pregnant women were eating less fish than non-pregnant women of the same age (Lando et al, 2012). A similar reaction was reported in the United Kingdom in 2023 in response to precautionary consumption advice that emphasized types of fish to limit and avoid for safety (Beasant et al, 2023). Twentyseven percent of those surveyed ate fish less often during pregnancy and four percent stopped eating fish altogether.…”
Section: )mentioning
confidence: 70%
“…Subsequent survey research by FDA also indicated that pregnant women were eating less fish than non-pregnant women of the same age (Lando et al, 2012). A similar reaction was reported in the United Kingdom in 2023 in response to precautionary consumption advice that emphasized types of fish to limit and avoid for safety (Beasant et al, 2023). Twentyseven percent of those surveyed ate fish less often during pregnancy and four percent stopped eating fish altogether.…”
Section: )mentioning
confidence: 70%
“…Amongst those consuming oily fish only 7.3% of children, 12.8% of teenagers, and 15.6% of young adults aged 20-29 years fell in line and met oily fish recommendations (30). A further analysis of survey data within this publication (data from 10 publications) found that EPA and DHA intakes were lower than guidelines, with children, teenagers, females, and pregnant women presenting some of the largest dietary gaps (30). The PEAR (31) study conducted with 598 women before/during pregnancy found that women who ate fish prior to pregnancy reduced their intakes of both oily and white fish during pregnancy, with some avoiding it altogether.…”
Section: Intakes Of O3lc-pufasmentioning
confidence: 89%
“…Given rising sustainability and toxicological concerns in the aquaculture sector research into possible alternative sources of O3LC-PUFAs has become a priority, to help plug the gap between supply and demand (42,88). Dietary intakes of O3LC-PUFAs largely remain to be insufficient in relation to the optimisation of health and cognitive outcomes (29,30,43). Historical evidence shows that fresh aquatic plants and seaweed were chewed such as red, green, and brown seaweeds and most likely consumed during Mesolithic and Neolithic time periods indicating that wild food resources were ingested before a switch to domesticated resources (93).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations